Follicle-stimulating hormone linked to cognitive decline and amyloid burden in postmenopausal women - Wang, Sheng-Min; Jeong, Chaiho; Um, Yoo Hyun; Kang, Dong Woo; Kim, Sunghwan; Lee, Soyoung; Lee, Chang Uk; Aizenstein, Howard J.; Baek, Ki-Hyun; Lim, Hyun Kook (Frontiers in Aging Neuroscience, 2026)
IntroductionWomen have a higher risk of developing Alzheimer’s disease (AD) than men, with hormonal changes during menopause being a potential factor. However, the exact relationship between these hormonal changes, cognitive function, and AD pathology is not fully understood. This study investigates the differential associations between serum follicle-stimulating hormone (FSH) and estradiol levels with cognitive function and cerebral amyloid-βeta (Aβ) deposition, quantified using amyloid positron emission tomography, in postmenopausal women across the spectrum from cognitively normal aging to AD dementia.MethodsA total of 884 postmenopausal women, aged 60 years or older, were enrolled in the study. Participants were classified into three groups based on their cognitive function: cognitively normal (CN), mild cognitive impairment (MCI), and AD dementia.ResultsHigher FSH levels were associated with poorer cognitive performance and greater cerebral Aβ deposition in postmenopausal women. FSH levels were highest in women with AD dementia, followed by those with MCI, and lowest in CN participants. No significant relationship was observed between estradiol levels and cognitive outcomes or Aβ burden. Further analysis showed a positive correlation between FSH levels and global as well as regional cerebral Aβ deposition. Mediation analysis indicated that FSH’s impact on cognitive function was mediated by cerebral Aβ burden. Estradiol levels, however, had no significant association with either cognitive performance or Aβ pathology.DiscussionElevated FSH, not low E2, is linked to cognitive decline and Aβ pathology in postmenopausal women. FSH may be a key risk factor for cerebral Aβ deposition and cognitive decline in older women. Further research is needed to elucidate the mechanisms involved and explore hormonal interventions for AD.